2021
DOI: 10.1103/physrevb.103.054203
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in a non-Hermitian Aubry-André-Harper model

Abstract: The Aubry-André-Harper model provides a paradigmatic example of aperiodic order in a one-dimensional lattice displaying a delocalization-localization phase transition at a finite critical value V c of the quasiperiodic potential amplitude V . In terms of the dynamical behavior of the system, the phase transition is discontinuous when one measures the quantum diffusion exponent δ of wave-packet spreading, with δ = 1 in the delocalized phase V < V c (ballistic transport), δ 1/2 at the critical point V = V c (dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 84 publications
(121 reference statements)
1
48
1
Order By: Relevance
“…In recent years, the impact of non-Hermiticity on localization transitions in AAH-type and Maryland-type quasicrystals have been explored [78,. The non-Hermitian effects are introduced by either setting the onsite quasiperiodic potential to be non-Hermitian [78,[81][82][83], or making the hopping amplitudes between adjacent lattice sites to be nonreciprocal [84,85]. In these models, it was found that the non-Hermitian terms could induce PT -transitions of the energy spectrum from real to complex (or the opposite), together with localizationdelocalization transitions of the eigenstates.…”
Section: A Quasicrystal Modelsmentioning
confidence: 99%
“…In recent years, the impact of non-Hermiticity on localization transitions in AAH-type and Maryland-type quasicrystals have been explored [78,. The non-Hermitian effects are introduced by either setting the onsite quasiperiodic potential to be non-Hermitian [78,[81][82][83], or making the hopping amplitudes between adjacent lattice sites to be nonreciprocal [84,85]. In these models, it was found that the non-Hermitian terms could induce PT -transitions of the energy spectrum from real to complex (or the opposite), together with localizationdelocalization transitions of the eigenstates.…”
Section: A Quasicrystal Modelsmentioning
confidence: 99%
“…* stefano.longhi@polimi.it Non-Hermiitan skin effect induced by static or fluctuating disorder has been also predicted [14,64,65]. The impact of non-Hermiticity in crystalline systems with disorder has been investigated in several works as well (see, for instance, [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] and references therein). A landmark model revealing the interplay between the skin effect and disorder is provided by the Anderson model of localization in a one-dimensional lattice with asymmetric hopping amplitudes [1,[68][69][70]73], introduced by Hatano and Nelson in a few pioneering works more than two decades ago [68,69].…”
Section: Introductionmentioning
confidence: 99%
“…The Anderson localization can occur for lattice with disorder and long-range aperiodic order [24][25][26][27][28][29]. In recent years, there are growing attentions on the interplay of non-Hermitian physics and disorder effect [30][31][32][33][34][35][36][37][38][39]. One * Electronic address: slzhu@nju.edu.cn line of work is the characterization and classification of matter phase in terms of disorder [16,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Other topics concern cooperation with coherent control techniques [42]. Disorder, or quasiperiodicity leads to exotic behaviors, including localization-delocalization transition under the PT symmetry breaking [43][44][45], generalized mobility edges [34] and anomalous particle transport [33], among which the non-Hermitian Aubry-André-Harper (AAH) model provides as a paradigmatic example. However, yet most works only concentrate on non-Hermitian Hamiltonian problems, systems resting on Liouvillians are still rarely studied.…”
Section: Introductionmentioning
confidence: 99%